From Transaction to Transformation: Explaining the Leadership Shift on EU Sanctions Policy Against Russia - Vadym Zheltovskyy (Studia Europejskie, 2023)
The article examines the leadership shift toward the EU sanctions policy against Russia in context of ongoing reconsideration of status quo that was caused by full-scale Russia’s invasion of Ukraine. The author draws attention to the transformation of the EU political leadership and their vision on the matter of foreign policy-making as a response to Russian aggression. Particular focus is put on the comparative analysis of competition outcomes between transactional and transformational viewpoints on sanction policy against Russia in years 2014–2021 and since February 2022.